Experimental Investigation of Pomegranate Peel and Grape Seed Powder Additives on the Rheological and Filtration Properties of Un-Weighted WBM - Amory, Noor Sabeeh; Almahdawi, Faleh H.M. (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
The chemical additives used to enhance the properties of drilling mud cause damage to humans and the environment. Therefore, it is necessary to search for alternative additives to add them to the drilling mud. Thus, this study investigates the effects of pomegranate peel and grape seed powders as natural waste when added to un-weighted water-based mud. The test includes measurements of the rheological properties and filtration, as well as the alkanity and density of the drilling mud. The results showed a decrease in PH values ​​with an increase in the concentrations of pomegranate peel or grapeseed, and a decrease in mud density with an increase in powders of pomegranate peel and grape seed concentrations that resulted from the formation of foam. The rheological properties appeared with increasing except for the plastic viscosity. Grape seed powders reduce the filter cake thickness required to solve drilling problems caused by an increase in the mud cake thickness. From the laboratory results, it’s possible to use powders of pomegranate peel and grape seed as additives to reduce plastic viscosity and filtrate volume.